Ingestion and Egestion of Microplastics by the Cladoceran Daphnia magna: Effects of Regular and Irregular Shaped Plastic and Sorbed Phenanthrene - Frydkjær, Camilla Krogh; Iversen, Niels; Roslev, Peter (Bulletin of environmental contamination and toxicology, 2017)
The presence of microplastics in aquatic ecosystems is of increasing global concern. This study investigated ingestion, egestion and acute effects of polyethylene microplastics in Daphnia magna . Fate of regular shaped microplastic beads (10–106 µm) were compared with irregular shaped microplastic fragments (10–75 µm). Daphnia magna ingested regular and irregular microplastic with uptake between 0.7 and 50 plastic particles/animal/day when exposed to microplastic concentrations of 0.0001–10 g/L. Egestion of irregular fragments was slower than that of microplastic beads. The EC50 for irregular microplastic was 0.065 g/L whereas microplastic beads were less inhibitory. The potential of microplastic to act as vector for hydrophobic pollutants was examined using [ 14 C]phenanthrene as tracer. Polyethylene microplastic sorbed less [ 14 C]phenanthrene compared to natural plankton organisms (bacteria, algae, yeast). As microplastics are much less abundant in most aquatic ecosystems compared to plankton organisms this suggests a limited role as vector for hydrophobic pollutants under current environmental conditions.